Therapeutic Interference With Vascular Calcification—Lessons From Klotho-Hypomorphic Mice and Beyond - Lang, Florian; Leibrock, Christina; Pelzl, Lisann; Gawaz, Meinrad; Pieske, Burkert; Alesutan, Ioana; Voelkl, Jakob (Frontiers in Endocrinology, 2018)
Medial vascular calcification, a major pathophysiological process leading to cardiovascular disease and mortality, involves osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells (VSMCs). In chronic kidney disease, osteo-/chondrogenic transdifferentiation of VSMCs and, thus, vascular calcification is mainly driven by hyperphosphatemia resulting from impaired elimination of phosphate by the diseased kidneys. Hyperphosphatemia with subsequent vascular calcification is a hallmark of klotho-hypomorphic mice, which are characterized by rapid development of multiple age-related disorders and early death. In those animals, hyperphosphatemia results from unrestrained formation of 1,25(OH)2D3 with subsequent retention of calcium and phosphate. Analysis of klotho-hypomorphic mice and mice with vitamin D3 overload uncovered several pathophysiological mechanisms participating in the orchestration of vascular calcification and several therapeutic opportunities to delay or even halt vascular calcification. The present brief review addresses the beneficial effects of bicarbonate, carbonic anhydrase inhibition, magnesium supplementation, mineralocorticoid receptor blockage and ammonium salts. The case is made that bicarbonate is mainly effective by decreasing intestinal absorption, and that carbonic anhydrase inhibition leads to metabolic acidosis, which counteracts calcium phosphate precipitation and VSMC transdifferentiation. Magnesium supplementation, mineralocorticoid receptor blockage and ammonium salts are mainly effective by interference with osteo-/chondrogenic signaling in VSMCs. It should be pointed out that the, by far, most efficient substances are ammonium salts, which may virtually prevent vascular calcification. Future research will probably uncover further therapeutic options and, most importantly, reveal whether these observations in mice can be translated into treatment of patients suffering from vascular calcification, such as patients with chronic kidney disease.